Crayfishes (Decapoda : Cambaridae) of Oklahoma: identification, distributions, and natural history - Morehouse, Reid L.; Tobler, Michael (Zootaxa, 2013)
We furnish an updated crayfish species list for the state of Oklahoma (United States of America), including an updated and illustrated dichotomous key. In addition, we include species accounts that summarize general characteristics, life coloration, similar species, distribution and habitat, life history, and syntopic species. Current and potential distributions were analyzed using ecological niche models to provide a critical resource for the identification of areas with conservation priorities and potential susceptibility to invasive species. Currently, Oklahoma harbors 30 species of crayfish, two of which were recently discovered. Eastern Oklahoma has the highest species diversity, as this area represents the western distribution extent for several species. The work herein provides baseline data for future work on crayfish biology and conservation in Oklahoma and surrounding states.